PERANCANG BUKU POP-UP BERBAGAI MACAM BENDA, HEWAN, DAN TANAMAN MENGGUNAKAN SOFTWARE GRAFIS SEBAGAI MEDIA PENUNJANG PEMBELAJARAN PADA SEKOLAH DASAR DI KABUPATEN KUNINGAN - Fadhly Abdillah; Deny Martha; Deni Yuli Saputro (Jurnal Digit, 2018)
Abstract Lack of supporting media in the learning process in a school or other department, can affect the success or failure of the learning process. Media in the learning process actually it is sufficient, such as book, tutorial poster, and props privided by teacher. But still needed innovation so the learning process more interesting. In 7th theme book for class 1 elementary school is about things, animals, and plants around us, the childrens must can recognize all things, animals, and plants around us. So, with this pop-up book, the childrens have fun to reading book. With this book , teachers and students still have the problems to reach the purpose of learning. With improving book to Pop-up book, students will be interesting in learning and understand the material. Pop-up book is very usefull for childrens, because make the childrens easy to umderstand what the teachers said. And then, with the pop-up book the childrens can improve their creativity and imajination with the different interface. Pop-up book, have much more picture design than text. So with this pop-up book, students will be interesting to read because the visual of this book. With this pop-up book the teacher be facilitated in the learning process, and the students will interest to learning using this book, so the purpose of the learning can be achieved. Keywords: Book, Pop-up, Education, Things, Animals, Plants